Characteristics of the Entrepreneurial Environment in European Union Countries: a Comparative Analysis - Valentina Diana Rusu; Angela Roman (EIRP Proceedings, 2016)
The major importance of entrepreneurship for economic growth, competitiveness, creating jobs and innovation is widely recognized. The objectives of our paper are to realize a comparative analyze of the characteristics of entrepreneurship in the EU countries, as well as to identify the perceptions about it. For our analysis we use the values for the key indicators obtained from data base and reports of Global Entrepreneurship Monitor. Also, in order to realize the comparison we use the classification of EU countries according to their development level. The results obtained show that there are important differences between the EU countries regarding entrepreneurial activity, but also among the countries in the same group. The countries with a higher economic development have a better entrepreneurial environment than those less developed. Regarding the perception about entrepreneurship, our results show that almost half of working age population from EU observe good opportunities in the region for starting a business, but almost as many of them affirm that a big constrain in starting a business would be their fear of failure. Overall, the results of our research allow identifying the measures that would be required to be taken by policy makers to stimulate entrepreneurship in European countries.